Fermentação, cinética e degradação ruminal em ovinos alimentados com fontes de carboidratos associadas ao óleo - Morgado, Eliane da Silva [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP]; Galzerano, Leandro [UNESP]; Malheiros, Euclides Braga [UNESP]; Santos, Viviane Correa [UNESP]; Cattelan, Jose Wanderley [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The objective this work was to evaluate the degradation, fermentation and kinetics of passage rumen fluid en sheep fed diets containing different carbohydrate associated with the oil. Four rumen cannulated sheep were allotted in 4 x 4 latin square. The treatments consisted of diets with high neutral detergent soluble fiber and diets with high starch associated or not with 4,2% of oil. Incubation times were 3, 6, 12, 24, 48, 72, 96 and 120 hours and ruminal fluid was collected at 0, 2, 4, 6, 8, 10, 12, and 24 hours after feeding. Diets high neutral detergent fiber soluble resulted in greater degradation of dry matter, crude protein, neutral detergent fiber soluble and starch, and higher pH values, butyric acid production, dilution rate and ruminal recycling compared with diets high starch content. The inclusion of 4,2% oil the different carbohydrate sources had no influence on the fermentation kinetics and degradation of the fiber. High content of neutral detergent soluble fiber in the diet favors the ruminal fermentation compared to the high starch content.
Fermentation, kinetics and ruminal degradation in sheep fed with carbohydrate sources associated with oil
Keywords: Starch; Degradability; detergent neutral soluble fiber; Corn; Ruminal parameter; citrus pulp